Analisis Praktek Akad Musaqah pada Petani Karet dalam Tinjauan Ekonomi Islam di Desa Cempaka Jaya - Ligery, Finny; Khasanah, Nurul; Subandi, Subandi (Bulletin of Community Engagement, 2022)
Research on cooperation in Musaqah contracts in Cempaka Jaya Village, East Menggala District, Tulang Bawang Regency aims to analyze and find out about muamalah as applied to land owners and land cultivators. The research method used by researchers is a qualitative method with a case study approach, using data collection techniques from interviews, observations and literature studies. Using non-participant observation where researchers only observe the work of rubber farmers who own land and cultivate land in the field and for interviews using structured interviews. The practice of musaqah contracts implemented in Cempaka Jaya Village, East Menggala District, Tulang Bawang Regency is not yet fully in accordance with sharia', because there are still rubber farmers who deviate from the sharia'. The effect of the cooperation in the musaqah agreement has a small influence so that the community is not prosperous, because they cannot meet their daily needs due to natural factors that influence rubber latex and also the cheap price of rubber. The calculation of profit sharing is applied in accordance with the agreement in the ijab qabul. Keywords: Practice Musaqah Agreement, Islamic Economics